1985
DOI: 10.1038/jcbfm.1985.81
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Intracellular Changes during Supercarbia: An in vivo 31P Nuclear Magnetic Resonance Study in Rats

Abstract: Summary: 31p nuclear magnetic resonance (NMR) spec troscopy was used noninvasively to measure in vivo changes in intracellular pH and intracellular phosphate metabolites in the brains of rats during supercarbia (P aco2 "" 400 mm Hg). Five intubated rats were mechanically ventilated with inspired gas mixtures containing 70% CO2 and 30% 02' Supercarbia in the rat was observed to cause a greater reduction in cerebral intracellular pH (pH) and increase in Peo2 than observed in other experiments with rats after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

1986
1986
2001
2001

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(28 citation statements)
references
References 31 publications
1
27
0
Order By: Relevance
“…How ever, despite a mean pH of 6.92, we found no evi dence of damage in glc + FDP-treated cells, whereas glc-treated cultures (without FDP but with the same low pH) had abnormal appearances, lower protein concentrations, and high LDH contents in their medium. This suggests that pH per se does not always damage cells, which was also shown by the in vivo studies of Litt et al (1985). They showed that hypercarbia-induced brain intracellular pH of 6.45 did not damage the CNS of adult rats if the concentration of ATP in their brains remained nor mal.…”
Section: Discussionmentioning
confidence: 72%
“…How ever, despite a mean pH of 6.92, we found no evi dence of damage in glc + FDP-treated cells, whereas glc-treated cultures (without FDP but with the same low pH) had abnormal appearances, lower protein concentrations, and high LDH contents in their medium. This suggests that pH per se does not always damage cells, which was also shown by the in vivo studies of Litt et al (1985). They showed that hypercarbia-induced brain intracellular pH of 6.45 did not damage the CNS of adult rats if the concentration of ATP in their brains remained nor mal.…”
Section: Discussionmentioning
confidence: 72%
“…2. lar pH during occlusion is not exclusively respon sible for preventing recovery. One rat in group B, for example, recovered despite a pH as low as that seen in group C; moreover, nonischemic rats with experimental hypercarbia resulting in brain pH val ues of 6.5 measured by NMR also recovered meta bolically (Litt et al, 1985). More important are the extent and rate of pH decrease and lactate accumu lation during the first 10-20 min of reperfusion.…”
Section: Discussionmentioning
confidence: 90%
“…The importance of acidosis in the etiology of ir reversible cell injury is weakened by the results ob tained from in vivo and in vitro studies. Litt et al (1985) lowered cerebral pHi by 0.63 units in rats ventilated with 70% CO 2 without producing appar-ent biochemical injury. Siemkowicz and Hansen (1981) exposed normo-and hyperglycemic rats to 10 min of global ischemia.…”
Section: Discussionmentioning
confidence: 99%